Pancasila Student Profile of Elementary School Students in Class IV Phase (B) Through Critical Thinking Skills on Fraction Material - Firda Nur Rifatussulikha; Feny Rita Fiantika; Susi Hermin Rusminati (Formosa Journal of Sustainable Research, 2023)
Critical thinking skills are one of the project elements in the Pancasila profile in order to strengthen the profile of Pancasila students, especially critical thinking. Students who are able to think critically are students who have objective critical thinking skills who are able to effectively process, analyze and evaluate the information obtained to draw conclusions. This research aims to describe the Pancasila student profile of class IV phase (B) students by using critical thinking skills in understanding fraction material. The approach used in this research is a qualitative approach, which is based on actual data obtained from the field. The subjects of this research were 21 students from class IV B at SDN Kepuhwisata 1, consisting of 12 girls and 9 boys. This research focuses on students who have high critical thinking abilities (TAM). The data collection methods used involved written tests, unstructured interviews, and documentation. The written test was carried out twice, the first was a mathematics ability test which consisted of 5 questions and was tested on all class IV B students. The aim was to identify each student's critical thinking abilities. The second test is a critical thinking test which is taken by three students. These students are students who are selected and have been selected from the first test. Next, the three subjects will be analyzed in detail and interviews will be conducted